2015
DOI: 10.18517/ijaseit.5.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and acute toxicity studies of ethanol extract from Pedada (Sonneratia caseolaris) fruit flour (PFF)

Abstract: Studies on the phytochemical and acute toxicity of pedada fruit flour (PFF) were carried out. In acute toxicity test, oral administration of the extract to Swiss albino mice at four levels dose, i.e. 0, 10.50; 15.75 and 21.00 g/kg body weight. Phytochemical analysis of the ethanol extract of PFF showed the presence of saponins, sapogenins, terpenoids, flavonoids, tannins, polyphenols. Phytochemicals such as alkaloids were not detected. The results of acute toxicity (LD50) showed that the ethanol extract of PFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…The results of this study showed that biscuit preferred by the panelist was with substitution 20% of PFF (biscuit PFF) and 20% of LFF (biscuit LFF). The previous results showed that PFF and LFF contains dietary fibers and bioctive compounds, such as flavonoid, phenol, tannin (Jariyah et al, 2015), vitamin C, and minerals (Jariyah et al, 2014). Those compounds are good for health and can be used for substitution in biscuit products.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that biscuit preferred by the panelist was with substitution 20% of PFF (biscuit PFF) and 20% of LFF (biscuit LFF). The previous results showed that PFF and LFF contains dietary fibers and bioctive compounds, such as flavonoid, phenol, tannin (Jariyah et al, 2015), vitamin C, and minerals (Jariyah et al, 2014). Those compounds are good for health and can be used for substitution in biscuit products.…”
Section: Introductionmentioning
confidence: 99%
“…10 This plant contains secondary metabolites such as flavonoids, 11 phenolics, terpenoids, steroids, and alkaloids. 3,12,13 S. caseolaris is a plant to bear fruit and includes numerous small seeds are covered with flesh. It has bioactive components including Alkaloids, saponins, terpenoids, tannins, flavonoids, steroids, and derivates of benzene carboxylate, 8,12 and commonly consumed by the community in Java and Kalimantan island.…”
Section: Introductionmentioning
confidence: 99%
“…3,12,13 S. caseolaris is a plant to bear fruit and includes numerous small seeds are covered with flesh. It has bioactive components including Alkaloids, saponins, terpenoids, tannins, flavonoids, steroids, and derivates of benzene carboxylate, 8,12 and commonly consumed by the community in Java and Kalimantan island. The ripe fruit has a distinctive flavor and pharmacological properties similar to other parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biscuits can be enriched with carrot extracts to increase β-carotene for health benefits [5]. Mangrove fruit flour (MFF) is rich in dietary fiber and bioactive compounds can potentially contribute to the development of functional food products [6], [7], [8]. Therefore, MFF can be mixed with wheat flour as a composite flour to make biscuits.…”
Section: Introductionmentioning
confidence: 99%